The effects of fish oil omega-3 fatty acid supplementation on mental health parameters and metabolic status of patients with polycystic ovary syndrome: a randomized, double-blind, placebo-controlled trial - Mehrdad Amini; Fereshteh Bahmani; Fatemeh Foroozanfard; Zahra Vahedpoor; Amir Ghaderi; Mohsen Taghizadeh; Hassan Karbassizadeh; Zatollah Asemi (Journal of Psychosomatic Obstetrics and Gynecology, 2020)
Objective This study was conducted to evaluate the effects of fish oil omega-3 fatty acid supplementation on mental health parameters and metabolic status of women with polycystic ovary syndrome (PCOS). Methods This randomized double-blind, placebo-controlled trial was conducted on 60 women with PCOS, aged 18–40 years old. Participants were randomly assigned into two groups to receive either 2 × 1000 mg/day fish oil omega-3 fatty acid (n = 30) or placebo (n = 30) after lunch for 12 weeks. Metabolic profiles were quantified at baseline and after the 12-week intervention. Results Compared with the placebo, omega-3 fatty acid intake led to a significant improvement in Beck Depression Inventory [β (difference in the mean outcomes measures between treatment groups after intervention) –1.05; 95% CI: –1.84, –0.26; p = .01], general health questionnaire (β –1.68; 95% CI: –3.12, –0.24; p = .02) and depression anxiety and stress scale (β –2.03; 95% CI: –3.60, –0.46; p = .01). Omega-3 fatty acid supplementation significantly decreased serum insulin levels (β –2.09 µIU/mL; 95% CI: –3.77, –0.41; p = .01), homeostasis model of assessment-insulin resistance (β –0.74; 95% CI: –1.13, –0.34; p < .001), total testosterone (β –0.23 ng/mL; 95% CI: –0.39, –0.06; p = .03) and hirsutism (β –0.75; 95% CI: –1.17, –0.33; p = .001), and significantly increased the quantitative insulin sensitivity check index (β 0.01; 95% CI: 0.003, 0.02; p = .008) compared with the placebo. Additionally, omega-3 fatty acid intake resulted in a significant decrease in high sensitivity C-reactive protein (β –1.46 mg/L; 95% CI: –2.16, –0.75; p < .001) and malondialdehyde (β –0.28 µmol/L; 95% CI: –0.52, –0.05; p = .03); also significant rises in plasma total glutathione (β 59.09 µmol/L; 95% CI: 7.07, 111.11; p = .02) was observed compared with the placebo. Omega-3 fatty acid supplementation did not change other metabolic parameters. Conclusion Overall, omega-3 fatty acid supplementation for 12 weeks to patients with PCOS had beneficial effects on mental health parameters, insulin metabolism, total testosterone, hirsutism and few inflammatory markers and oxidative stress.